Tafsir Alquran dan Praktik Politik Umat Islam Indonesia Perspektif Tafsir al-Azhar dan Tafsir al-Mishbah - Mujahidin, Anwar (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2017)
It is a common agreement that Muslims in Indonesia accept nation state as a system which is not based solely on religion, but religion, at the same time, could be the main pillar and source of value in its principal. This paper is aimed at putting Indonesian Qur’anic exegesis into consideration, Hamka’s Tafsir al-Azhar and M. Quraish Shihab’s Tafsir al-Mishbah, related to the issue of state power and government. It attempts to delve into the values constructed by both exegetes on the Qur’anic verses related to the principles of the power and how those values are applied in the nation state formation. The results of the study suggests that some of Qur’anic values composed by both exegetes is: realization of nation state in a well-organized bureaucratic system, that is manifested in a good leadership, which is based on high competency selected based on democratic system selection (mushawarah). These values are able to be exemplified by both exegetes in nation-state frames with reference to cooperative and critical attitude towards the government.